Public Asset Management Companies : A Toolkit - Cerruti, Caroline (Washington, DC: World Bank, 2016)
This toolkit is designed for policy makers and stakeholders who are considering the establishment of a publicly funded asset management company (AMC). An AMC is a statutory body or corporation, fully or partially owned by the government, usually established in times of financial sector stress, to assume the management of distressed assets and recoup the public cost of resolving the crisis. AMCs were first used in the early 1990s in Sweden (Securum) and the United States (the RTC), and again during the Asian crisis (for instance, Danaharta in Malaysia, KAMCO in the Republic of Korea). The 2008 financial crisis marked a renewal of the use of this tool to support the resolution of financial crises (for instance, NAMA in Ireland, SAREB in Spain). The toolkit does not address broader bank resolution issues. It has a narrow focus on the specific tool of a public AMC established to support bank resolution, and with the objective of providing insight on the design and operational issues surrounding the creation of such AMCs. It seeks to inform policy makers on issues to consider if and when planning to establish a public AMC through: · An analysis of recent public AMCs established as a result of the global financial crisis · Detailed case studies in developed and emerging markets over three generations · A toolkit approach with questions and answers, including questions on design and operations that are critical for authorities confronted with the issue of whether to establish an AMC · An emphasis on “how to” that is, a practical versus a principled approach. The toolkit is structured as followed: Part I summarizes the findings on the preconditions, the design, and the operationalization of public AMCs. Part II provides case studies on three generations of AMCs, whose lessons are embedded in Part I. The case studies cover emerging and developed markets, and have been selected based on the lessons they offer.